22.5k views
2 votes
Solve the following equation, answer as a reduced, mixed number. Then place the correct number in the box provided. 4(2x -3) + 8(x - 4) = 2(2x + 6

1 Answer

2 votes

Answer:

4 2/3

Explanation:

4(2x -3) + 8(x - 4) = 2(2x + 6)

Distribute

8x -12 + 8x -32 = 4x +12

Combine like terms

16x - 44 = 4x+12

Subtract 4x from each side

16x-4x-44 =4x-4x+12

12x-44 = 12

Add 44 to each side

12x-44+44 = 12+44

12x = 56

Divide each side by 12

12x/12 = 56/12

x = 14 / 3

Changing to a mixed number

x = 4 2/3

User Galaktor
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.